Design of lightweight concrete arch tiles as permanent formwork for upper floor slab by using polystyrene beads - Nurshamiera, Muhamad Fudzi (2015)
Nowadays in Malaysia, many contractors and developers are still struggling to catch up with the current pace of development, especially in meeting country's demand, as conventional construction methods still work. Although traditional practice, this conventional method has several disadvantages such as high labor and material costs, and especially, a tendency not to change production of construction waste. Therefore, to overcome these weaknesses, permanent formwork using lightweight concrete is chosen as an alternative solution. In short, the new technology existence in construction to overcome this problem is permanent formwork using lightweight concrete which is more useful than conventional methods in terms of effectiveness of the functions, lighter, safety features and productivity. The main objective of this study is to determine the density and compressive strength of lightweight concrete to be used as arch slab by using polystyrene beads. The tests will be conducted is to find compressive strength and the displacement of the arch slab. All the procedures are prepared accordingly, to assure the research objectives are applicable, and to secure proper sequence and smooth running of the entire flow, from start until end. Six samples will provided, which three of them are 50mm and the rest is 75mm. All six samples of the slab tile are concreted at Heavy Structure Laboratory, Universiti Malaysia Pahang (UMP) and compressive strength test also conducted at same laboratory. Meanwhile the flexural test is conducted at Tensile Laboratory. From the theoretically calculation of arch tile of 50mm arch rise have highest horizontal and vertical force compared than arch rise 75mm with difference average load 1.267kN. While displacement of arch rise 50mm have highest displacement compared than arch tile of 75mm with difference displacement 0.463mm because of its geometry. Meanwhile, the density of fresh concrete with and without EPS also has difference about 68 kg/m3. As conclusion, EPS can be used as extenuating agent in concrete. However, from the observation, we can hardly distinguish which of this arch tile is stronger. Besides that, the development of the graph pattern for each sample is not consistent, thus explains the indifferences of the load bearing capacity.